2021
DOI: 10.3390/molecules26195860
|View full text |Cite
|
Sign up to set email alerts
|

Lycoperoside H, a Tomato Seed Saponin, Improves Epidermal Dehydration by Increasing Ceramide in the Stratum Corneum and Steroidal Anti-Inflammatory Effect

Abstract: Tomatoes are widely consumed, however, studies on tomato seeds are limited. In this study, we isolated 11 compounds including saponins and flavonol glycosides from tomato seeds and evaluated their effects on epidermal hydration. Among the isolated compounds, tomato seed saponins (10 µM) significantly increased the mRNA expression of proteins related to epidermal hydration, including filaggrin, involucrin, and enzymes for ceramide synthesis, by 1.32- to 1.91-fold compared with the control in HaCaT cells. Tomato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 61 publications
(118 reference statements)
0
10
0
Order By: Relevance
“…Our results indicated that RC supplementation effectively reduces participants' EI. Although ceramides were known to promote inflammatory responses, new evidence suggests otherwise [54,55]. In vitro study demonstrated that ceramides can effectively reduce the expression of inflammatory enzymes and cytokines, predominantly inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and tumor necrosis factor-α (TNF-α) by inhibiting NF-κB activation [54].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that RC supplementation effectively reduces participants' EI. Although ceramides were known to promote inflammatory responses, new evidence suggests otherwise [54,55]. In vitro study demonstrated that ceramides can effectively reduce the expression of inflammatory enzymes and cytokines, predominantly inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and tumor necrosis factor-α (TNF-α) by inhibiting NF-κB activation [54].…”
Section: Discussionmentioning
confidence: 99%
“…Significant increases in TEWL are commonly observed in dry skin diseases, such as AD [30], xerosis, and psoriasis [31]. We previously reported the moisturizing effects of isolated steroidal saponins from tomato seeds and β-sitosterol 3-O-glucoside from rice on TEWL in RHEK models [32]. In the present study, all GlcCer[d18:2(4E,8Z)] (1, 3, 7, 10, and 13) significantly attenuated TEWL, whereas GlcCer[t18:1(8Z)] (2, 5, 9, and 12), GlcCer[d18:2(4E,8E)] (4, 8 and 11), and GlcCer[t18:1(4E)] (6) did not.…”
Section: Discussionmentioning
confidence: 99%
“…[21] The seed of the tomato contains a lot of phytoconstituent especially low molecular weight, which is known as steroidal alkaloid saponin. [21,22] Lycoperoside H (LH) is a well-known alkaloidal saponin and active ingredient of tomatoes. [22][23][24] The activity of the LH is similar to the other alkaloidal saponin such as esculeosides and lycoperosides.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Lycoperoside H (LH) is a well-known alkaloidal saponin and active ingredient of tomatoes. [22][23][24] The activity of the LH is similar to the other alkaloidal saponin such as esculeosides and lycoperosides. Saponins already show various biological activities such as wound healing and anti-inflammatory effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation